Demographic Factors in the System of Building a Social State (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The author elucidate the effects of demographic factors on the formation of a stable economic, intellectual, political and social development of the Ukrainian state. It clearly depicts the role of demography as the main issue for strategic asset allocation, that is, long-term investments and as a result numerous consequences for the economy and financial system of Ukraine. The main idea is to change the vector of reforms to ensure the sustainability of the population and create appropriate conditions for life support, it will lead to improved economic dynamics of the Ukrainian state as a whole.